Hubungan Pengetahuan dengan Kecemasan Ibu Hamil Primigravida terhadap Berhubungan Seks selama Kehamilan di Wilayah kerja Puskesmas Sei Langkai Kota Batam - Susanti Susanti (stikes dharma husada bandung, 2021)
Research conducted by the National Family Planning Coordinating Board (BKKBN) states that basic knowledge of health is limited. 57.89% of respondents do not know the meaning of sexuality. Respondents' attitudes towards sexuality health promotion based on myths in society provide a relatively good indication, but the nuances of doubt are also relatively felt. Only 58.33% of information about sexuality was obtained through health workers, and 31.67% obtained from other sources. Knowledge as a physical tool which is very important for the formation of action from experience and research has proven that one's behavior towards knowledge will be more lasting than without being based on knowledge. One of the factors that causes sexuality is not disturbed by knowledge and knowledge. The purpose of this study is to determine the relationship. Knowledge of trimester I primigravida pregnant women having sex during pregnancy in the work area of ​​the Sei Langkai Health Center, Batam City. This research is cross sectional, the research area is the work area of ​​Puskesmas Sei Langkai, Batam City, the study population of pregnant women who do ANC using the sampling technique Accidental Sampling, the number of samples is 48 respondents. The instrument used for the independent variable and the dependent variable using a questionnaire that has been tested for the validity used is chi-square analysis. The results of the research conducted from 48 respondents who had good knowledge and performed stimulation well, namely 30 responses (62.5%), p-value 0.003 <0.05.